STRATEGI KOMUNIKASI BADAN PENANGGULANGAN BENCANA DAERAH MAGETAN DALAM UPAYA PENGURANGAN RISIKO BENCANA COVID-19 DI PONDOK PESANTREN AL FATAH TEMBORO (Universitas Negeri Surabaya, 2023)
This study explains the communication strategy of the Magetan Regional Disaster Management Agency in an effort to reduce the risk of the Covid-19 disaster at the Al Fatah Temboro Islamic Boarding School and the stance taken by the Magetan Regional Disaster Management Agency in dealing with the Covid-19 virus. To achieve the above objectives, qualitative research methods are used with this type of case study research. Data collection techniques used are observation, interviews and documentation. The data analysis tool in this study was interactive analysis and then analyzed through the process of data collection, data reduction, data presentation, and drawing conclusions. The presentation of the data in this study is in the form of writing and explains what it is according to the data in the field. The results of this study conclude that based on the research that has been conducted, the application of a communication strategy with a persuasive communication model in handling Covid-19 has been carried out by the Magetan Regency Disaster Management Agency and has had a positive impact on the Al Fatah Temboro Islamic Boarding School Keywords : Covid-19, BPBD, Communication Strategy, Pondok Pesantren.